Exploratory Analysis of Autologous Stem Cell Transplantation In Newly Diagnosed Multiple Myeloma Patients Treated with Bortezomib, Lenalidomide, Dexamethasone: A Small-Scale Real-World Cohort Study in Viet Nam - Dung, Phu Chi; Duong, Trinh Thuy; Trang, Bui Nguyen Thuy; Minh Thang, Nguyen Tran (Journal of Neonatal Surgery, 2025)
Aims: To assess whether the benefits of autologous stem cell transplantation continue to be maintained in practice when combined with bortezomib, lenalidomide, and dexamethasone in the treatment of newly diagnosed multiple myeloma patients. Methods: A retrospective cohort study of 48 patients who were new diagnosed with multiple myeloma, treated with regimen bortezomib, lenalidomide, dexamethasone (borte, lena, dexam) at Blood Transfusion and Hematology hospital, in which 23 patients were treated in combination with autologous stem cell transplantation. Results: The study found that the VGPR rate in the autologous group was higher than in the non-autologous group, but this difference was not statistically significant. The median PFS time was not reached at the end of the study, with a median follow-up of 36 months. The 2-year PFS probability was 78.3% for the group with and without autologous stem cell transplantation, and 58.7% for the group with and without transplantation. The median OS time was 91.7% for the transplantation group and 88.8% for the non-transplantation group. The group with autologous stem cell transplantation had a significantly higher rate of complications than the group without transplantation. No deaths occurred in either group, including those over 65 years old. Conclusion: The combination treatment of bortezomib, lenalidomide, and dexamethasone is effective and safe for newly diagnosed multiple myeloma patients, including those without transplantation and those eligible for autologous stem cell transplantation. Early stem cell collection is recommended for patients with combined treatment with autologous transplantation.